Specjalistyczne turnusy terapeutyczne dla jąkających się – organizacja i efekty terapii - Bijak, Elżbieta (Logopedia Silesiana, 2012)
Specialist therapeutic holiday for those who stammer – organization and effects of therapy The author presents the effects of therapy of people taking part in specialist therapeutic holiday for those who stammer, which constitute a coherent system of therapeutic activities performed in accordance with the assumptions of “The Modified Programme of Psychophysiological Therapy of Stammering People” by dr M. Chęciek. The material contains the results of diagnoses (preliminary and final) of the Level of Logophobia and the Frequency level of stammering by adult participants of the holiday XI/XII 2008, VIII 2009, XI/XII 2009.